Expressive arts therapy for hospitalized children: a pilot study measuring cortisol levels - Garret Yount; Kenneth Rachlin; Jane Siegel (MDPI AG, 2013)
This pilot study aimed at assessing the feasibility of capturing physiological evidence of reduced stress for hospitalized children following expressive arts therapy. Twenty-five patients were offered a novel form of expressive arts therapy, termed Healing Sock Creatures, during their stay in the hospital. Saliva samples were collected at two times in the afternoon for the purpose of measuring salivary cortisol levels. The patients were randomly assigned to two groups, a treatment group or a wait-list control group. A trend of decreased cortisol levels was apparent following therapy in the treatment group and concurrent steroid treatment, which is common in intensive care units, does not appear to interfere with the ability to measure decreased cortisol levels following therapy. Our results support the design of a formal study to assess physiological biomarkers of stress in hospital settings. To our knowledge, this is the first in-patient study assessing a biomarker of stress following expressive arts therapy for children